Performance Assessment of Japanese Electricity and Gas Companies during 2002–2018: Three DEA Approaches - Toshiyuki Sueyoshi; Mika Goto (Energies, 2021)
This study has compared Japan’s major electricity and gas companies in terms of their corporate performance measures from 2002 to 2018 using three types of Data Envelopment Analysis (DEA) approaches. We develop a new type of efficiency measures and indexes for DEA and then compare the performance of major electric power companies and city gas companies by examining a recent data set that include years after the Fukushima Daiichi Nuclear Power Plant accident. The data set incorporates the number of patents as an output that represents companies’ capability for technology innovation to investigate intertemporal changes of efficiency through index measures. The results provide us with two important findings. First, the electricity industry has experienced long-term difficulty due to the nuclear plant disaster; while the gas industry experienced less difficulty from the accident. Second, both industries have been gradually improving performance measures in recent years. However, the gas industry has outperformed the electricity industry. From the results, this study discusses important policy implications for Japan’s energy utility industry and academic research on the industry.